Open access to journal articles in dentistry: Prevalence and citation impact. (April 2016) - Hua, Fang; Sun, Heyuan; Walsh, Tanya; Worthington, Helen; Glenny, Anne-Marie
Abstract: Objectives: To investigate the current prevalence of open access (OA) in the field of dentistry, the means used to provide OA, as well as the association between OA and citation counts. Methods: PubMed was searched for dental articles published in 2013. The OA status of each article was determined by manually checking Google, Google Scholar, PubMed and ResearchGate. Citation data were extracted from Google Scholar, Scopus and Web of Science. Chi-square tests were used to compare the OA prevalence by different subjects, study types, and continents of origin. The association between OA and citation count was studied with multivariable logistic regression analyses. Results: A random sample of 908 articles was deemed eligible and therefore included. Among these, 416 were found freely available online, indicating an overall OA rate of 45.8%. Significant difference in OA rate was detected among articles in different subjects ( P  < 0.001) and among those from different continents ( P  < 0.001). Of articles that were OA, 74.2% were available via self-archiving ('Green road' OA), 53.3% were available from publishers ('Gold road' OA). According to multivariable logistic regression analyses, OA status was not significantly associated with either the existence of citation ( P  = 0.37) or the level of citation ( P  = 0.52). Conclusions/clinical significance: In the field of dentistry, 54% of recent journal articles are behind the paywall (non-OA) one year after their publication dates. The 'Green road' of providing OA was more common than the 'Gold road'. No evidence suggested that OA articles received significantly more citations than non-OA articles.